Waiter Joe : uma solução tecnológica - Hartmann, Jáder (2018)
This meta-paper describes a possible solution for some problems faced by bars and parties currently located in the region. The steps to the development of an application with functions to assist in commercial transactions and establish a communication with the client. Also, generate essential information to identify frequency problems on weak days as well explanation of strong days, all, storage in a database which can be accessed through a system developed for the bar.